Maternal vitamin D insufficiency and risk of adverse pregnancy and birth outcomes: A systematic review and meta-analysis of longitudinal studies. - A Kofi Amegah; Moses K Klevor; Carol L Wagner (PLoS ONE)
Background Three previous reviews on the association of vitamin D insufficiency in pregnancy with preterm birth (PTB) and stillbirth were limited in scope and deemed inconclusive. With important new evidence accumulating, there is the need to update the previous estimates and assess evidence on other clinically important outcomes such as spontaneous abortion and Apgar score. We conducted a systematic review and meta-analysis to evaluate the quality and strength of the available evidence on the relations between vitamin D nutritional status, and pregnancy and birth outcomes. Methods PubMed and Scopus databases were searched from their inception to June, 2015 with no language restrictions imposed. Eighteen longitudinal studies satisfied the inclusion criteria. Random effects model was applied in computing the summary effect estimates and their corresponding 95% confidence intervals. Results Serum 25(OH)D levels <75 nmol/l was associated with 83% (95% CI: 1.23, 2.74) and 13% (95% CI: 0.94, 1.36) increased risk of PTB measured at <32-34 weeks and <35-37 weeks, respectively. An inverse dose-response relation was observed for both PTB outcome. Serum 25(OH)D levels <75 nmol/l was also associated with 11% increased risk of spontaneous PTB (<35-37 weeks; RR = 1.11; 95% CI: 0.75, 1.65) with a dose-response relation also noted. Vitamin D insufficiency was not associated with risk of spontaneous abortion and stillbirth (RR of 1.04 [95% CI: 0.95, 1.13] and 1.02 [95% CI: 0.96, 1.09], respectively), as well as short gestational length (ES = -0.24, 95% CI: -0.69, 0.22), and low Apgar score. Conclusions We found vitamin D insufficiency to be associated with risk of PTB. Regarding spontaneous abortion and stillbirth, the available evidence suggest no association with low vitamin D levels. The evidence on vitamin D nutrition and Apgar score is conflicting and controversial. Overall, the experimental evidence uncovered was small and weak. Hence, the benefits of vitamin D supplementation during pregnancy should be further evaluated through rigorous intervention studies.